NutsFor a process-oriented model to simulate nutrient and isotope tracer cycling in forest ecosystems. (September 2017) - van der Heijden, G.; Belyazid, S.; Dambrine, E.; Ranger, Jacques; Legout, A.
Abstract: We developed a process-oriented model called NutsFor that simulates nutrient cycling of major cations (Ca, Mg, K, Al, NH4, Na) and anions (NO3, SO4, Cl) and the stable isotope tracers for each of the respective elements at the scale of an ecosystem (isotopic fractionation are not simulated). We tested the ability of NutsFor to reproduce major element and stable isotope tracer ( 26 Mg and 44 Ca) cycling with the data from 35-yr old beech stand in France. NutsFor correctly reproduced the measured trends in soil solution chemistry for most major elements. The high similarity between modeled and measured distribution of 26 Mg and 44 Ca tracers in the ecosystem provided a unique and robust way to evaluate the hypotheses grounding the model and study the efficiency of Mg and Ca cycling at this very nutrient-poor site. Highlights: NutsFor model simulates major element & isotope tracer cycling in forest ecosystems. Isotope data provided a unique and robust way to evaluate model hypotheses. Mg and Ca cycling time scales were simulated with NutsFor. Mg and Ca cycling is very slow and conservative in this forest ecosystem.